State-dependent sliding mode control for three-phase induction motor drives - Fizatul Aini, Patakor (2014)
This research focuses on investigation and evaluation of the robust speed control for threephase induction motor. A sliding mode control, which offers great potential to deal with uncertainties such as parameter variation and external load disturbances, is examined. The main obstacle of conventional sliding mode control is caused by discontinuous function of high control activity which is known as chattering phenomenon. In this research, this chattering phenomenon is significantly reduced by a newly developed algorithm. A fast sigmoid function with varying boundary layer algorithm is designed as a state-dependent to replace the discontinuous function in conventional sliding mode control as well as to avoid steady state error compare with the use of fixed boundary layer. It is known that the switching gain of sliding mode control is proportional to the chattering level, and normally a large switching gain is applied to handle the uncertainties. This research proposes a state-dependent sliding mode control which is the switching gain is proportional to the sigmoid function of the sliding mode controller. As a result, the boundary layer and the switching gain will change depending on uncertainties of the motor drives system. In this research, the induction motor is controlled by vector control strategy, using indirect field orientation and Space Vector Pulse Width Modulation technique. Simulation result have proved that the proposed state-dependent sliding mode control was able to deal with external load disturbances as well as effectively free from chattering phenomenon compared to conventional sliding mode control. Finally, experimental investigation is performed in order to confirm the theoretical and simulation findings. The proposed algorithm and the vector control strategy are developed in digital signal processing board. The experimental results have confirmed that the state-dependent sliding mode control is superior with regard to external load disturbances and variation in the reference speed setting when compared to PI speed control and conventional sliding mode control.